Is Metaverse in education a blessing or a curse: a combined content and bibliometric analysis - Tlili, Ahmed; Huang, Ronghuai; Shehata, Boulus; Liu, Dejian; Zhao, Jialu; Metwally, Ahmed Hosny Saleh; Wang, Huanhuan; Denden, Mouna; Bozkurt, Aras; Lee, Lik-Hang; Beyoglu, Dogus; Altinay, Fahriye; et al. (Smart learning environments, 2022)
The Metaverse has been the centre of attraction for educationists for quite some time. This field got renewed interest with the announcement of social media giant Facebook as it rebranding and positioning it as Meta. While several studies conducted literature reviews to summarize the findings related to the Metaverse in general, no study to the best of our knowledge focused on systematically summarizing the finding related to the Metaverse in education. To cover this gap, this study conducts a systematic literature review of the Metaverse in education. It then applies both content and bibliometric analysis to reveal the research trends, focus, and limitations of this research topic. The obtained findings reveal the research gap in lifelogging applications in educational Metaverse. The findings also show that the design of Metaverse in education has evolved over generations, where generation Z is more targeted with artificial intelligence technologies compared to generation X or Y. In terms of learning scenarios, there have been very few studies focusing on mobile learning, hybrid learning, and micro learning. Additionally, no study focused on using the Metaverse in education for students with disabilities. The findings of this study provide a roadmap of future research directions to be taken into consideration and investigated to enhance the adoption of the Metaverse in education worldwide, as well as to enhance the learning and teaching experiences in the Metaverse.